2022
DOI: 10.2147/jmdh.s372000
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of COVID-19 Vaccination in Low- and Middle-Income Countries

Abstract: Background WHO reported that 5.5 million people died in the world because of COVID-19. One of the efforts to mitigate the pandemic is administrating the vaccines globally. Objective The objective of this study was to review cost-effectiveness analysis of COVID-19 vaccination in low- and middle-income countries (LMICs). Methods We searched PubMed and EBSCO for the eligible studies with inclusion criteria using cost-effectiveness analysis, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…On the other hand, although vaccination may be a critical achievement in this challenging situation to address this health problem, there are concerns regarding the costs of preparation. When dealing with the costs of public vaccination, which is different according to the type of vaccine and estimated to be approximately $50 billion to save the world, usually there is no limitation for high‐income countries, whereas the majority of countries are not able to access sufficient amount especially low and middle‐income countries 11,19,20 . So, a big dilemma is providing sufficient financial sources to implement vaccination programs for a large number of populations in a short time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although vaccination may be a critical achievement in this challenging situation to address this health problem, there are concerns regarding the costs of preparation. When dealing with the costs of public vaccination, which is different according to the type of vaccine and estimated to be approximately $50 billion to save the world, usually there is no limitation for high‐income countries, whereas the majority of countries are not able to access sufficient amount especially low and middle‐income countries 11,19,20 . So, a big dilemma is providing sufficient financial sources to implement vaccination programs for a large number of populations in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…When dealing with the costs of public vaccination, which is different according to the type of vaccine and estimated to be approximately $50 billion to save the world, usually there is no limitation for high‐income countries, whereas the majority of countries are not able to access sufficient amount especially low and middle‐income countries. 11 , 19 , 20 So, a big dilemma is providing sufficient financial sources to implement vaccination programs for a large number of populations in a short time. Nevertheless, it is supposed that this huge cost prioritizes and prevents more devastating economic impacts of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…This gap is particularly striking when one considers the credit given to the vaccine by the global health community in epidemic response, especially in low-and middle-income countries (LMICs), where the vaccine is considered one of the most cost-effective public health interventions (Utami et al, 2022). The global evaluation of the response to the COVID-19 pandemic showed that vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was effective in reducing case fatality, particularly in those vulnerable due to age and/or comorbidities, and in reducing human-to-human transmission and circulation of the virus, that is, end the pandemic (Sachs et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence suggests that vaccination against COVID-19 is remarkably effective in preventing the need for hospital treatment and premature deaths [5] and lowering the costs associated with the delivery of healthcare services [6], which is especially important in middle-income countries like Serbia. The analysis of mortality and immunisation status has found higher mortality in countries with lower vaccination coverage [7].…”
Section: Introductionmentioning
confidence: 99%